Nano-laminated Ti3SiC2 synthesized by cost-effective semi-melting process. Issue 12 (15th June 2021) - Kim, Byeong Geun; Nou, Changwan; Bae, Sang Hyun; Choi, Soon-Mok
Abstract: Titanium silicon carbide (Ti3 SiC2 ) with unique nano-laminated structures was successfully synthesized using an arc melting process with composite pellets of individual elements (Ti, Si, and C). The arc melting process was repeated and process parameters were controlled to form homogeneous high-purity Ti3 SiC2 phases. In contrast with conventional arc melting, Ti3 SiC2 phases were prepared by the semi-melting of source pellets, which maintained almost their original forms. This semi-melting process is industrially worthwhile, to keep costs down, because additional manufacturing processes are unnecessary or minimized. The distribution and size of pores and density in the products were controlled by varying the experimental parameters, and the temperature-dependent electrical properties of Ti3 SiC2 -MAX phases were investigated also.